Achievement of organisational goals and motivation of middle level managers within the context of the two-factor theory - Jansen, A; Samuel, MO (My University, 2014)
The ever dynamic nature of the world of work requires that organisations constantly review factors that energise managers (particularly middle level managers) towards achievement of set goals. This category of employees translates strategic decisions by top management into action through the operational employees. They (middle level managers) therefore serve as a link between top management and the lower level employees thus making their role to be of outmost importance to the survival and competitiveness of any organisation thus necessitating the need of our present study. The study adopted a survey research method using quantitative research design. A measuring instrument with a Cronbach alpha coefficient of above 0.70 was developed and used to collect primary data. Non-random sampling technique using purposive/convenience sampling procedure was employed in deriving a sample size of 250 middle-level managers who participated in the survey. Main hypotheses were formulated and tested using the Chi-Square test to determine the level of association between intrinsic and extrinsic motivational variables and achievement of organisational goals by middle level managers. Results show that both intrinsic and extrinsic motivational variables impacted significantly on achievement of organisational goals by this category of managers. Based on this finding, we therefore recommend that organisations should combine both intrinsic and extrinsic motivational variables in the design of goal achievement strategy for middle level managers.
Keywords: Top Management; Intrinsic motivation; Extrinsic motivation; Private sector organisation